Kendala Guru pada Pembelajaran Matematika di Era Pandemi Covid-19 - Nilza Humaira Salsabila; Nourma Pramestie Wulandari; Ulfa Lu’luilmaknun; Dwi Novitasari (Fakultas MIPA Universitas Nahdlatul Wathan Mataram, 2021)
The aim of this study is to describe how the conditions of learning carried out online during the pandemic. Then what are the challenges faced and the advantages felt by teachers through online learning, as well as solutions from teachers related to increasing the effectiveness of learning mathematics during the pandemic. This research is quantitative-qualitative research. The subjects in this study amounted to 11 teachers of mathematics. The data collection instrument used a questionnaire regarding teacher responses about learning mathematics in the pandemic era. The results show that the applications used by teachers to assist the learning process include WhatsApp, Google Classroom, and others. However, there are several obstacles faced by teachers during the online learning process, for example limited facilities and the delivery of learning materials that are not optimal. The government needs to provide the needs of schools and students for online learning. Teachers also state that learning videos can help students learn during the pandemic.